THE EFFECT OF NONI LEAF EXTRACT ON THE PERFORMANCE OF MALE BALI DUCKS - L. A. S., Apriyanti; Siti, N. W.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the effect of noni leaf extract on the performance of male Bali ducks aged 0-8 weeks. The study used a completely randomized design (CRD) with three treatments and five replications, each replication using two male Bali ducks with a weight of 63.6 ± 1.96 g ducks. The treatment given is; P0 (drinking water + without noni leaf extract), P1 (drinking water + 2ml noni leaf extract) and P2 (drinking water + 4ml noni leaf extract). The variables observed in this study were initial body weight, ration consumption, drinking water consumption, final body weight, weight gain and Feed Conversion Ratio. The results showed that giving 2 ml and 4 ml of noni leaf extract had no significant effect (P>0.05) on drinking water consumption, final body weight, weight gain and FCR, but had a significantly different effect (P<0.05) on ration consumption. Based on this research, it can be concluded that the administration of noni leaf extract as much as 2ml-4ml/head/day can not improve the performance of male Bali ducks.   Keywords: Bali duck, noni leaves, performance